Uji Kadar Lemak Keju Cheddar dengan Variasi Bahan Baku (Sapi, Kambing) serta Variasi Jenis Starter (Streptococcus lactis, Rhizophus oryzae) - Solikah Ana Estikomah (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2017)
Cheese is dairy product. Microorganism are most widely used in starter, especially the cheese starter is a group of lactic acid bacteria (LAB), which is capable of producing acid Bacteri acid lactit (BAL) often used as starter in cheesemaking. This purpose of this study is variation of milk and starter in to improve the quality.In this research the ceddar making was conducted the varation milk and starter. cheddar cheese produced in this study analyzed the value of curd,water, and fat contained with Anava then followed by DMRT 5% level of significance. The best quality in the cheddar cheese at K2B2 , the randemen value 21.66, water value 38.66 and fat value 34.51.